Hydration Characteristics of Paddy - Mohanty, S N; Bal, Satish; Dash, Sanjay K; Panda, M K (Journal of Agricultural Engineering, 2002)
The hydration characteristics of paddy (Cv. Parijata) were studied for soaking under atmospheric and elevated pressures and for steaming operations. Soaking treatments under atmospheric condition were carried out at 40, 50, 60 and 70degreeC water temperature. The pressure levels for hydrostatic soaking were 2.0, 4.0 and 6.0 kg/cmÂ² with a constant water temperature of 70degreeC. Steaming was carried out at 0.5, 1.0. 1.5,2.0 and 2.5 kg/cmÂ² pressure levels. For all the studies, 3 levels of initial moisture contents were taken. The soaking temperature and pressure and steaming pressure greatly influenced the moisture absorption by the grain and, thus, affected the time requirement. The diffusion coefficients, diffusion constants and activation energy for moisture diffusion were also calculated for the different treatments. The diffusion coefficient was independent of moisture content and showed Arrhenius type relationship with absolute temperatures of soaking and steaming. Empirical relationships were developed to predict the moisture gain by paddy at any time and process condition.